Peran teknologi dalam meningkatkan berbicara bahasa arab - Hidayat, Asmar (Maliki Interdisciplinary Journal, 2025)
Technology has become a crucial tool in enhancing Arabic speaking skills, offering various opportunities for learners to engage in interactive and immersive learning experiences. The advancement of digital technology has introduced numerous applications, online platforms, and artificial intelligence-based tools that facilitate the acquisition of the Arabic language. This study aims to examine the role of technology in improving Arabic speaking proficiency by analyzing various technological tools, including mobile applications, social media platforms, virtual classrooms, and AI-powered chatbots.The study highlights the effectiveness of digital applications such as language learning apps, speech recognition software, and online courses that enable learners to practice speaking skills directly. Social media platforms like YouTube, WhatsApp, and Telegram also play a significant role in supporting language learners by providing interactive and collaborative learning environments. Moreover, AI-powered chatbots and speech recognition systems have emerged as effective tools in improving pronunciation and fluency through real-time feedback.The findings show that technology significantly contributes to the enhancement of Arabic speaking skills, especially for non-native speakers who have limited exposure to Arabic-speaking environments. The use of interactive media and artificial intelligence helps learners overcome language barriers and build confidence in speaking. In addition, online courses and virtual language exchange programs allow students to engage in meaningful conversations with native speakers, thus accelerating their language acquisition process. In conclusion, the integration of technology in Arabic language learning has proven to be an effective strategy for improving speaking skills.